(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2013)
This paper examines the topic of universal human responsibilities. The United Nations claims that "human rights simultaneously entail both rights and obligations."1 This statement implies that if human beings have fundamental rights by virtue of their personhood, they also have fundamental responsibilities to other persons.2 A right is something to which an individual has a just claim, a morally correct demand for something that is due or believed to be due. Responsibility refers to the duty (a moral or legal obligation) of being answerable for the consequences of an act or function.3 The underlying premise of this paper is that people acting responsibly will create an environment where it is less likely their rights will be violated; responsibilities complement rights.